2013
DOI: 10.1177/0734242x13500518
|View full text |Cite
|
Sign up to set email alerts
|

The greenhouse gas and energy balance of different treatment concepts for bio-waste

Abstract: The greenhouse gas (GHG) and energy performance of bio-waste treatment plants been investigated for three characteristic bio-waste treatment concepts: composting; biological drying for the production of biomass fuel fractions; and anaerobic digestion. Compared with other studies about the environmental impacts of bio-waste management, this study focused on the direct comparison of the latest process concepts and state-of-the-art emission control measures. To enable a comparison, the mass balance and products w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…From an environmental point of view, the properly functioning biogas plants generating energy from renewable energy sources have a significant advantage over aerobic stabilization/composting of biodegradable waste [21]. However, the results of the economic analysis of anaerobic digestion and aerobic stabilization show that the profitability of both processes to a large extent depends on the situation on the energy market.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From an environmental point of view, the properly functioning biogas plants generating energy from renewable energy sources have a significant advantage over aerobic stabilization/composting of biodegradable waste [21]. However, the results of the economic analysis of anaerobic digestion and aerobic stabilization show that the profitability of both processes to a large extent depends on the situation on the energy market.…”
Section: Discussionmentioning
confidence: 99%
“…This study analyzed two alternative sources of industrial and agricultural wastes to fill the second digester. In the first option the feeding of 11 278 t/year of industrial wastes into the digester was assumed to reach the required level of dry matter (35%, after adding fresh water and/or leachate) as well as an appropriate carbon to nitrogen ratio (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The waste would be acquired from two sites located at a distance of 12 km and 35 km from the plant.…”
Section: Objectives and The Methodsmentioning
confidence: 99%
“…Need more work to promote environmentally sound waste disposal and support greenhouse gas mitigation by different means such as food loss, organic waste diversion, waste reduction, and the acceptance of treatment as well as disposal technologies that collect biogas and landfill gas (Ortner et al, 2013).…”
Section: Think About Climate Change and The Environmentmentioning
confidence: 99%
“…Home composting is a suitable treatment option for organic wastes such leftovers of raw fruit and vegetables from the technical and environmental point of view, as documented by Colon et al (2010). Composting, biomass fuel production, and anaerobic digestion contributes to GHG emission savings, and so they sound as valid alternatives to be considered for biowaste treatment (Ortner et al 2013). Andersen et al (2010) found that GHG emission of home composting units (cone-shaped, made of recycled polyethylene and polypropylene) is similar in magnitude as for centralized composting plants in Denmark.…”
Section: Literature Reviewmentioning
confidence: 99%